2017
DOI: 10.32637/orli.v47i1.191
|View full text |Cite
|
Sign up to set email alerts
|

Radiological anatomy analysis of uncinate process, concha bullosa, and deviated septum in chronic rhinosinusitis

Abstract: Background: Risk factors of chronic rhinosinusitis include epithelial disease related to disturbanceof mucociliary transport system, anatomical variations obstructing the ostiomeatal complex anddysfunction of neural regulation.Purpose: To find the prevalence of deviated septum, concha bullosa andlateral deflection of the uncinate process in ipsilateral chronic rhinosinusitis.Methods: A retrospectivestudy of computed tomographic (CT) scans of chronic rhinosinusitis patients who were not cured by6 weeks of maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…[44] Tuli IP et al (2013) also reported 30% deflection of the prosessus unsinatus, of which 24% was medial deflection and found a significant relationship between the variation in deflection and rhinosinusitis (p=0.033). [45] However, the study by Wardani RS et al (2017) stated that the lateral deflection (70.7%) was more dominant than the medial deflection (29.3%). The prevalence of lateral deflection that occurs towards ipsilateral maxillary sinusitis is 71.5% and from the results of statistical analysis, a significant relationship was found (p=0.03).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[44] Tuli IP et al (2013) also reported 30% deflection of the prosessus unsinatus, of which 24% was medial deflection and found a significant relationship between the variation in deflection and rhinosinusitis (p=0.033). [45] However, the study by Wardani RS et al (2017) stated that the lateral deflection (70.7%) was more dominant than the medial deflection (29.3%). The prevalence of lateral deflection that occurs towards ipsilateral maxillary sinusitis is 71.5% and from the results of statistical analysis, a significant relationship was found (p=0.03).…”
Section: Resultsmentioning
confidence: 98%
“…This is assumed because the lateral deflection of the prosessus unsinatus impairs the drainage of the maxillary sinus ostium due to narrowing of the infundibulum and causes ipsilateral maxillary sinusitis. [46] The second variation of the prosessus unsinatus assessed is the superior insertion variation of the prosessus unsinatus. Table 11 showed that 17 samples (13.3%) and 11 samples (8.6%) with type 1 insertion respectively had scores of 1 and 2 in the maxillary sinus.…”
Section: Resultsmentioning
confidence: 99%
“…41 While concha bullosa is pneumatization that occurs in the concha media and can narrow the semilunar hiatus and block the infundibular drainage, resulting in sinusitis. 42 The bullous conchae are small with a vertical height of less than 50% of the total median conchae as measured on a coronal CT scan. While the bullous conchae are said to be large if the vertical height is more than 50% with an increase in the volume of the media conchae.…”
Section: Resultsmentioning
confidence: 99%